Flexible Composite Films Made of EMAA- Na+ Ionomer: Evaluation of the Influence of Piezoelectric Particles on the Thermal and Mechanical Properties - Tita, Sandra P. S.; Magalhães, Fernão D.; Paiva, Diana; Bertochi, Maria A. Z.; Teixeira, Guilhermina F.; Pires, Ana L.; Pereira, André M.; Tarpani, José R. (My University, 2022)
Studies that aim to produce flexible films of composite materials based on ionomers-PZT, and volume fractions lower than 10% PZT, in order to monitor damage in aeronautical structures are seldom investigated. The growing emphasis on the use of polymers capable of self-healing after damage or activation by heating has motivated the application of self-healing ionomers as polymeric matrices in composites with piezoelectric particles aiming to monitor damage. Flexible composite films were developed based on the self-healing polymer matrix Surlyn® 8940 ionomer (DuPont™ —Wilmington, DE, USA) and PZT particles (connectivity 2-3) in volume fractions of 1, 3, 5 and 7%, with thickness around 50–100 µm. The choice of PZT volume fractions followed the preliminary requirement that establishes a final density, which is lower or at least close to the density of the materials used in aeronautical structures. Since the application of composites based on epoxy resin/carbon fibers has been increasing in the aeronautical segment, this material (with density lower than 1500 kg/m3) was chosen as a reference for the present work. Thus, due to self-healing (a characteristic of the matrix Surlyn® 8940) combined with recyclability, high flexibility and low thickness, the flexible composite films showed advantages to be applied on aeronautical structures, which present complex geometries and low-density materials. The manufactured films were characterized by SEM, XRD, DMA and mechanical tensile tests. The results were discussed mainly in terms of the volume fraction of PZT. X-ray diffraction patterns showed coexistent rhombohedral and tetragonal phases in the PZT particles-dispersed composite, which can potentialize the alignment of ferroelectric domains during polarization under strong electrical field, enhancing dielectric and piezoelectric properties toward sensing applications. DMA and tensile testing results demonstrated that the addition of PZT particles did not impair either dynamic or quasi-static mechanical performance of the flexible composite films. It was concluded that the PZT volume fraction should be lower than 3% because, for higher values, the molecular mobility of the polymer would suffer significant reductions. These findings, combined with the high flexibility and low density of the ceramic particle-filled thermoplastic polymer, render the developed flexible composite film a very promising candidate for strain and damage sensing in aeronautical structures.
Keywords: damage sensor; flexible composite films; flexible polymer films-PZT; ionomers